2016
DOI: 10.1103/physrevapplied.6.044019
|View full text |Cite
|
Sign up to set email alerts
|

Self-Affine Graphene Metasurfaces for Tunable Broadband Absorption

Abstract: Graphene has emerged as a promising platform for THz metasurfaces supporting electrically tunable deep-subwavelength plasmonic excitations. Here, we introduce a broadband graphene metasurface based on the Hilbert curve, a continuous, space-filling fractal. We demonstrate enhancement of graphene absorption over a broad frequency band (0.5-60 THz) with an average absorption level exceeding 20%. Owing to the continuous nature of the metasurface patterns, both absorption level and bandwidth can be controlled elect… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
33
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 76 publications
(33 citation statements)
references
References 64 publications
0
33
0
Order By: Relevance
“…It has been proved that the near-field characteristics and electromagnetic multipoles can be artificially tailored through plasmonic meta-structures. [5][6][7][8] Few years ago, toroidal dipole excitation was for the first time experimentally observed as the dominant term in the electromagnetic response of purposely designed metamaterials [9][10][11] in the microwave region. 12 Subsequently, the toroidal resonances have also been pushed to terahertz and optical frequencies with metallic and dielectric metamaterials.…”
mentioning
confidence: 99%
“…It has been proved that the near-field characteristics and electromagnetic multipoles can be artificially tailored through plasmonic meta-structures. [5][6][7][8] Few years ago, toroidal dipole excitation was for the first time experimentally observed as the dominant term in the electromagnetic response of purposely designed metamaterials [9][10][11] in the microwave region. 12 Subsequently, the toroidal resonances have also been pushed to terahertz and optical frequencies with metallic and dielectric metamaterials.…”
mentioning
confidence: 99%
“…For instance, graphene metasurfaces with both positive and negative graphene Hilbert metasurfaces of levels from I to V were investigated throughout the terahertz and mid-infrared range. [47] It was shown that graphene fractal metasurfaces can exhibit a tunable and broadband absorption. Multiple resonances in the fractal graphene metasurface were designed for the broadband response in terahertz regime.…”
Section: Functional Light Manipulations With Complex 2d Graphene Metamentioning
confidence: 99%
“…[30][31][32][33] Compared to the conventional plasmonic materials-noble metals, the plasmonic resonance of graphene resides in the technically important bands: terahertz and infrared frequencies. [15,[34][35][36][37][38][39][40][41][42][43][44][45][46][47][48][49] Graphene plasmons show much stronger confinement of light compared to that in noble metals. The light is localized in the vicinity of the atomic thin film, providing a novel platform to manipulate light in a 2D manner.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, graphene-based Fano resonance metasurfaces have been successfully proposed for light manipulating devices such as modulators [ 10 13 ], absorbers [ 14 , 15 ], slow-light devices [ 16 , 17 ], and cloaks [ 16 , 18 ], as well as others. In these devices, radiative losses were mitigated as a result of strong interaction between the monolayer graphene and the confined electric field in resonant gaps.…”
Section: Introductionmentioning
confidence: 99%